Digital Transformation and Schumpeterian Growth: Inter-Rationality in Open Innovation Dynamics and Finance - Ouyang, Huizi; Ur Rehman, Shafiq; Ness, Stephanie; Ahmad, Hussein; Altrawneh, Kalil; Allahham, Mahmoud; Ullah, Naqeeb (2025)
The ability to innovate is one of the most important factors causing economic progress, managing to improve competitive advantage for organizations, and helping to grow the GDP in general. This particular study analyzes the effects of digital transformation in conjunction with the theory of Schumpeterian, growth, and open innovation patterns regarding the innovation output, while paying special attention to inter-rationality as a moderator. However, although their importance is given fore, these factors especially from the empirical perspective have not been explored much in this specific combination. Primary data was collected from n = 300 respondents who were innovation managers, R&D and product development directors, chief technology officers, and other senior executives, respectively. The data was then analyzed using SEM-PLS technique. The results validate the assertion that digital transformation Schumpeterian growth and open innovation dynamics are strong predictors of innovation output. In particular, it is observed that transformation in the use of digital technology contributes to the impacts estimation of output innovations (β = 0.371, p < 0.001) and thus, an organization that integrates advanced forms of digital technology, is likely to achieve high levels of innovation. It is found that Schumpeterian growth has a positive effect on the innovation output as well (β = 0.395, p < 0.001), another entrepreneurial activity encompassed in this theory being unceasing development. Open innovation dynamics also increase the innovation output (β = 0.409, p < 0.001), which emphasizes the strategy of internal and external cooperation. Furthermore, inter-rationality acts as a significant moderator in the relations of these variables with innovation output, high interdisciplinary and cross-functional teamwork increasing these interactions. This study gives useful information to managers, researchers and policy makers regarding the need to encourage the use of digital technologies for enhancing entrepreneurial, efforts and enabling external collaborations. These results underscore the critical role of integrating advanced digital tranformation, fostering entrepreneurial activity, and leveraging external collaborations to enhance innovation capabilities. Managers are encouraged to invest in digital tools, nurture a culture of cross-functional collaboration, and adopt open innovation strategies to maximize organizational performance. Policymakers can use these insights to design frameworks that support innovation-driven economic development.